2016
DOI: 10.1049/el.2016.2742
|View full text |Cite
|
Sign up to set email alerts
|

Wideband mixer exploiting and compensation technique

Abstract: A novel wideband down‐conversion mixer is proposed for multi‐standard wireless applications between 100 MHz and 2.5 GHz. A transconductance stage with two pairs of compensatory transistors is adopted for high linearity. Differing from the ordinary differential multi‐gated transistor technique utilised in Gilbert mixer, the design proposed concerns about both gm″ and gm compensation of the transconductance stage in order to improve both input‐referred third‐order intercept point (IIP3) and 1 dB gain compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The fan power PF is calculated using Eq. (2). The thermal power of each air treatment process in the air handling unit is calculated using Eq.…”
Section: E = P · Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The fan power PF is calculated using Eq. (2). The thermal power of each air treatment process in the air handling unit is calculated using Eq.…”
Section: E = P · Tmentioning
confidence: 99%
“…The setpoint is usually selected, based on the peak-load, even though the majority of operation is under lower loads [2]. For this reason, all algorithms (Air conditioning priority, Airflow priority and Intake power optimization) have the duct static pressure reset.…”
Section: Control Algorithmsmentioning
confidence: 99%
“…-[ * ] Corresponding author, fxchen_qjy@hotmail.com Broadly speaking, there are various methods to remove the excess heat from PEMFC and keep the its temperature as desired; for example, liquid cooling [12,13], air cooling [14,15], edge-cooling [16], phase change cooling [17], combined oxidant and coolant flow [18], and natural convection cooling [19]. Among these thermal management methods, water cooling of higher heat transfer coefficient is most widely used in high power PEMFC systems, especially for a power output of 80 kW or higher [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a three-component aza-Wittig reaction was used to synthesize quinolinone [10], thienopyrimidinone [11], triazolopyrimidinone [12], which have good biological activities. However, the attempt to obtain a series of chromenopyrimidione by this mean has not been reported.…”
Section: Introductionmentioning
confidence: 99%